1977
DOI: 10.1093/ajcn/30.5.704
|View full text |Cite
|
Sign up to set email alerts
|

Newborn body composition and its relationship to linear growth

Abstract: Anthropometric measurements were made on 4,952 newborns from a Peruvian urgan population. Newborns characterized by high subcutaneous fat and high muscle had significantly greater birth weights and recumbent lengths when compared to their counterparts with low subcutaneous fat and muscle. Similarly, newborns characterized by high muscle and low fat had significantly greater birth weights and recumbent lengths that newborns characterized by low muscle and high fat. It is postulated that an increase in newborn p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

1980
1980
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 26 publications
0
9
0
2
Order By: Relevance
“…Hashimoto et al 19 reported a correlation of 0.275 between maternal and offspring weights during the ®rst year of life. Three other studies 12,16,18 found that the offspring of obese mothers were heavier than those of nonobese mothers, but only after ages that varied from 6 months to 4 y. By contrast, ®ve studies, 17,20 ± 22 including a personal communication by Robert Whitaker, found no relationship between measures of maternal and offspring weight during the ®rst two years of life.…”
Section: Discussionmentioning
confidence: 97%
“…Hashimoto et al 19 reported a correlation of 0.275 between maternal and offspring weights during the ®rst year of life. Three other studies 12,16,18 found that the offspring of obese mothers were heavier than those of nonobese mothers, but only after ages that varied from 6 months to 4 y. By contrast, ®ve studies, 17,20 ± 22 including a personal communication by Robert Whitaker, found no relationship between measures of maternal and offspring weight during the ®rst two years of life.…”
Section: Discussionmentioning
confidence: 97%
“…Isso se deve ao fato de que o crescimento intra-uterino aumentado dos filhos de obesas é maior em massa corporal (maior incorporação de tecido adiposo) e não em altura, mantendo, portanto, uma média que não difere, estatisticamente, das médias de filhos de normais e desnutridas. Aliás, os estudos de Frisancho e col. 8 mostraram haver uma correspondência entre a quantidade de tecido adiposo da gestante e a do recém-nascido. Udall e col. 29 também obtiveram resultados semelhantes.…”
Section: Resultsunclassified
“…This work highlighted the important role that maternal nutritional status has on the trajectory of a child's prenatal and postnatal growth. Contrary to the prevailing notions of the time, Roberto's work showed that the fetal growth was not buffered from fluctuations in maternal nutritional status; but rather, that maternal undernutrition had a profound influence on childhood development and later health outcomes (Frisancho et al, 1977).…”
Section: Evolutionary and Adaptive Perspectives On Human Nutrition Anmentioning
confidence: 89%
“…In the 1970s and early-1980s, Roberto collaborated with colleagues at the Maternity Hospital in Lima to study the nutritional and developmental determinants of low-birth weight infants (Frisancho et al, 1977(Frisancho et al, , 1983(Frisancho et al, , 1984b(Frisancho et al, ,c, 1985. This work highlighted the important role that maternal nutritional status has on the trajectory of a child's prenatal and postnatal growth.…”
Section: Evolutionary and Adaptive Perspectives On Human Nutrition Anmentioning
confidence: 99%